Treatment of linear alkyl benzene sulfonate in an intermittent cycle extended aeration system - Mohammad Reza Samaei; Majid Nozari; Marziyeh Ansari Shiri; Mehdi Mokhtari; Asghar Ghasemi; Reza Rezaei Javanmardi (Shiraz University of Medical Sciences, 2017)
Background:Discharge of raw or treated wastewater containing linear alkyl benzene sulfonate (LAS) into the environment causes significant public health and environmental problems. The purpose of this study was the treatment of hospital wastewater using an intermittent cycle extended aeration system (ICEAS).Methods:Experiments were carried out on Yazd Shohaday-e-Kargar hospital wastewater treatment system and samples were collected in a 2 month period from the influent and effluent of the system. The used pilot study carried out consisted of two zones: pre-react and main react zones. They were divided using a baffle wall. Firstly, wastewater enters a pre-react zone and then through the opening at the bottom of the baffle wall it enters the main react zone. The cycle time and flow rate for the system were considered 6 h and 2 L/h, respectively. Then, the necessary tests were performed on the system's influent and effluent.Results:The removal of BOD5, COD, and LAS by ICEAS were 94.54%, 92.97%, and 84.99%, respectively. The averages of SVI, F/M, MLSS and MLVSS in the system were 113 mL/g, 0.086 Kg.BOD5/Kg.MLSS.d, 4327 mg/L and 3172 mg/L, respectively.Conclusions:This work showed the excellent efficiency of ICEAS to effectively remove BOD5, COD, and LAS from hospital wastewater. The results of this research can help to manage wastewater treatment in hospitals.